2022
DOI: 10.3390/ma15207159
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Study of PVD Coatings: TiN/AlTiN, TiN and TiAlSiN Used in Wood Machining

Abstract: In this paper, we analyze the possibilities of the protection of tools for wood machining with PVD (Physical Vapor Deposition) hard coatings. The nanolayered TiN/AlTiN coating, nanocomposite TiAlSiN coatings, and single layer TiN coating were analyzed in order to use them for protection of tools for wood machining. Both nanostructured coatings were deposited in an industrial magnetron sputtering system on the cutting blades made of sintered carbide WC-Co, while TiN single layer coating was deposited by evapora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The durability of the cutters was assessed by comparing the values obtained for the total path of contact of the cutter with the machined material for the uncoated and coated cutter [5]. A reported study in the literature [69] showed that the cutter durability (FABA firm) with TiN coatings deposited on WC-4.5 wt.% Co cutters using thermionic arc evaporation was only slightly higher (19%) than that of TiN-coated cutters for chipboard milling in the present work.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…The durability of the cutters was assessed by comparing the values obtained for the total path of contact of the cutter with the machined material for the uncoated and coated cutter [5]. A reported study in the literature [69] showed that the cutter durability (FABA firm) with TiN coatings deposited on WC-4.5 wt.% Co cutters using thermionic arc evaporation was only slightly higher (19%) than that of TiN-coated cutters for chipboard milling in the present work.…”
Section: Mechanical Propertiesmentioning
confidence: 99%